The features of studying and formation of domestic enterprises’ competitive advantages Особенности изучения и формирования конкурентных преимуществ отечественных предприятий - Trunina Irina M. (Problemi Ekonomiki, 2012)
The role of competitive advantages in providing enterprise competitiveness is shown. Their content is considered. The requirements to competitive advantages are proposed. The content of notion “sustained competitive advantages” is considered. The expediency of studying of domestic enterprises’ competitive advantages based on real conditions of their activity is shown. The existing domestic enterprises’ competitive advantages and causes of their gradual reduction are analyzed. The attention is paid to the processes in the enterprise activities that are not oriented directly on the consumer’s needs, but make the basis for enterprise competitive advantages formation. Показана роль конкурентных преимуществ в обеспечении конкурентоспособности предприятия, раскрыт их смысл. Представлены требования к конкурентным преимуществам. Раскрыто содержание понятия "устойчивое конкурентное преимущество". Показана целесообразность изучения конкурентных преимуществ отечественных предприятий с учетом реальных условий их деятельности. Проанализированы имеющиеся конкурентные преимущества отечественных предприятий и причины их постепенного утрачивания. Акцентировано внимание на тех процессах в деятельности предприятия, которые не ориентированы непосредственно на потребности потребителя, но именно с них начинают формироваться конкурентные преимущества предприятия.